Public Awareness for Antimicrobial Resistance from Escherichia coli Isolated from Beef Sold on Several Wet Market in Surabaya, Indonesia (Indian Journal of Public Health Research & Development, 2020)
Objective: This study aims to phenotypically identify and confirm the presence of multi-drug resistant(MDR) and Extended Spectrum Beta-Lactamase (ESBL) Producing Escherichia coli in the swab surfacesamples of beef using VITEK-2 method.Materials and Methods: Swab samples were taken from five wet markets: Pucang market, Wonokromomarket, Keputran market, Pabean market, and Manukan market; 10 swab samples of beef were collected fromeach market. Then, isolation and identification in terms of bacteria using selective media and biochemicaltest were conducted. Resistance testing using disc diffusion method was performed on 6 types of antibiotics:Ampicillin, Cefazolin, Ceftriaxone, Cefotaxime, Ceftazidime, Tetracyclin. Positive isolates resistant to ? 2types of Beta-Lactam antibiotics using disc diffusion method then were tested using VITEK-2 method.Results: Positive samples containing Escherichia coli are found in 29 samples out of 50 swab samples. Ofthe 29 Escherichia coli isolates, 17 isolates are found resistant to the disc diffusion method. After testingthose 17 isolates using VITEK-2 method, 5% (1/17) of ESBL-producing Escherichia coli are obtainedwhich is resistant to all Beta-Lactam antibiotics. Besides, this study also reveals that 35% (6/17) of theEscherichia coli are positive multidrug resistance. Those E.coli MDR are found to be resistant towardsantibiotic class Beta-Lactams, Aminoglycoside, Quinolon, and Sulfonamida.Conclusion: This study has encouraged the need for public awareness for the understanding that beeffrom wet market can be potential as reservoir to spread multi-drug resistant bacteria that can cause healthproblems in humans.
Keywords: MDR, ESBL, Escherichia coli, Beef, Vitek-2 System, Public Health